A STUDY OF MEDICATION PATTERNS AND FACTORS INFLUENCING MEDICATION USE IN PREGNANCY AT A RURAL HEALTH BLOCK - Dr. Saima Bashir; Dr. Sabah Nisar; Dr. Suhaib Qayoom; Dr. Hibba Dar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Pregnancy is a transformative phase for a woman's body, involving numerous significant physiological adjustments. Safely managing various health conditions that may emerge during pregnancy is paramount to ensure the well-being of both the expectant mother and the developing fetus. Understanding these prescribing patterns is essential to provide better guidance to expectant mothers and healthcare providers alike, ensuring that any medication use during pregnancy is both necessary and safe.Objective: To assess the patterns and factors affecting medication use along with prescription pattern during antenatal periods among pregnant women.Methods: A cross-sectional study was conducted in a rural health block spanning from July 2022 to December 2022. After securing verbal consent from antenatal women, we gathered data on patient demographics, co-existent medical conditions, medications prescribed, and recording the details in a predefined format. Descriptive statistics was used to analyze the baseline data, chi-square test was used for categorical variables and multivariate logistic regression was used for factors influencing drug prescription.Results: Among the 322 pregnant women who participated, 49% were primigravida; with a mean age of 27.6±3.1. Approximately 30% experienced at least one disease condition during pregnancy; with anemia (11%) being the commonest. The mean number of medications was 3.3 and 33.4% of participants received medication for a particular disease condition. Multivitamins/ minerals, antimicrobials and hormones were the commonest drug classes. Maternal age over 25 [(OR (CI): 1.26 (1.03–2.16) (p = .05)] and maternal illness [OR (CI) 2.03 (1.7–3.9) (p = .05)] were identified as factors affecting drug prescription.Conclusion: Most of our patients were multigravida over the age of 25. Vitamins and minerals were the most commonly prescribed medications, with antimicrobials being the most frequently recommended drug class for specific disease conditions. Maternal age exceeding 25 years and maternal health status were identified as influential factors in drug prescription.